2002
DOI: 10.1001/archpsyc.59.8.729
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Early Recovery From Major Depression Among Persons Admitted to Community-Based Clinics

Abstract: Initial depression severity and receiving adequate pharmacotherapy predict early recovery in individuals with major depression seeking outpatient treatment. A minority of persons receive intensive antidepressant treatment. Less severe personality dysfunction and being married predicts early recovery among persons with less severe depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 31 publications
4
57
3
Order By: Relevance
“…Our data were collected in patients receiving structured treatment, including weekly clinical monitoring. Thus, the course of symptom resolution we observed might represent what happens under optimal conditions rather than what typically happens under "usual care" conditions (36). By design, this analysis focuses on the outcome of first-line pharmacotherapy.…”
Section: Discussionmentioning
confidence: 98%
“…Our data were collected in patients receiving structured treatment, including weekly clinical monitoring. Thus, the course of symptom resolution we observed might represent what happens under optimal conditions rather than what typically happens under "usual care" conditions (36). By design, this analysis focuses on the outcome of first-line pharmacotherapy.…”
Section: Discussionmentioning
confidence: 98%
“…[13][14][15] Also the mean duration of index episode should be considered, because a proportion of patients might already be on the road to recovery at the beginning of the study, following the natural course of an untreated depression. At the opposite side, chronic depression (with episode length 42 years) is thought to respond poorly to treatments.…”
Section: Clinical Features Of Depressionmentioning
confidence: 99%
“…63 The low antidepressant dosages could be some variables that have been associated to a worse probability of treatment response. 13 The use of concomitant antipsychotics, sometimes needed in the clinical practice for depression, could strongly modulate the genetic influence to antidepressant response and should be avoided or at least separate subjects treated with concomitant antipsychotics from one treated with only antidepressant to evaluate genetic efficacy of antidepressant or antidepressant plus antipsychotics. Use of benzoziazepines also could influence outcome in particular ones or in case of change of dose during the study.…”
Section: Treatment Issuesmentioning
confidence: 99%
“…In an earlier study, we identified predictors of early (three-month) “recovery”, which was defined as two weeks with no or only minimal symptoms of depression (5). Early recovery was independently associated with less severe depression, adequate antidepressant treatment, being female, and married.…”
mentioning
confidence: 99%